Profile of Physical Conditions of Male Players of 3 State Volley Ball High School, Kaur Province Bengkulu - Hendra Jaya, Hendra Jaya (Jurnal Pendidikan, Kesehatan dan Olahraga, 2023)
This study aims to find out how well the physical condition of volleyball men's players at SMA Negeri 3 Kaur Regency. This research is a descriptive research with the method used is the survey method. The subjects of this study were all male volleyball players of SMA 3 Kaur Regency, which were 25 people. In this study using a test to determine the explosive power of leg muscles, arm muscle explosive power, agility, eye-hand coordination, flexibility and aerobic endurance related to the physical condition of male volleyball players. Sampling technique using purposive sampling. The instruments in the data collection of this study used tests and measurements of physical conditions which consisted of Vertical Jump Test, One Hand Medicine Ball Putt, Dodging Run Test, Tennis Ball Throwing, Flexiometer Test, Bleep Test. The data analysis technique used in this study is descriptive analysis techniques. Based on the results of the study, it can be seen that the physical condition of volleyball men's high school 3 Kaur Regency is categorized as very good at 8% (2 athlete), in the good category of 32% (8 athlete), in the moderate category, and less than 60% (15 athlete).